Maintenance PERIODICAL MAINTENANCE SERVICE VOLVO TRUCK FMX 440 DI PT. MADHANI TALATAH NUSANTARA - Darsini Darsini (Politeknik Negeri Ketapang, 2022)
Periodical Service is engine care to reduce the frequency of damage and duration of the injury. Good and efficient care can keep the tool's operating times, keep it in production, reduce the cost of unexpected damage. The purposes are to: (1) Perform Periodical Service activities during the activity, (2) Find when Periodical Service consists of PS 250, PS 500, PS 1000 and PS 2000, (3) Know the results of Periodical Service. Implementation of the Periodical Service fulfilled at PT. Madhani, especially in Volvo trucks, includes changing engine oil, changing engine oil filters, changing transmission oil and filters, changing final drive oil to the battery and electrical checks. With the Periodical Service data program showing PA (Physical Avelaibelity) results of over 95%, MTBF (Mean Time Between Failures) of over 3000 hours, and MTTR (Mean Time To Repair) of less than 20 hours, this is very effective and efficient to increasing production.